Public Sector Accounting and Auditing in Europe
XX, 258 p.
Keywords: The book provides an overview of the governmental accounting status quo in Europe by analysing the public sector accounting, budgeting and auditing systems in fourteen European countries. IT sheds light on the challenges faced by European countries as they move towards adoption of the European Public Sector Accounting Standards (EPSAS).